WEB-BASED ACADEMIC INFORMATION SYSTEM AT MUHAMMADIYAH AL AMIN SORONG JUNIOR HIGH SCHOOL - Melda Agnes Manuhutu (Electro Luceat, 2021)
Muhammadiyah Al Amin Sorong Junior High School is one of the private junior high schools located in Sorong City, West Papua. As a result of the COVID-19 outbreak, learning systems began to be done online from home. As a result, many complaints from teachers and students, especially new school year students in class VII about learning that is less understandable due to using software that has not been well socialized. Based on the background of the problem, the author researched and designed a web-based academic information system specialized in the collection of assignments and materials and assessment of grade VII students at Muhammadiyah Junior High School. The purpose of this research is to design a web-based academic information system for Muhammadiyah Al Amin Sorong Junior High School. The method of data collection carried out in this study is by interview method, observation and literature study, system development methods used, namely by prototype and website testing methods using blackbox testing, MySQL as a database, XAMPP as a local server and PHP as a programming language. The results of this study are web-based academic information systems for Muhammadiyah Al Amin Kota Sorong Junior High School which is dynamic in accordance with the system development methods used.